Development of a user-friendly mobile app for the national level promotion of the 4th generation district heating - Volkova, Anna; Latõšov, Eduard; Mašatin, Vladislav; Siirde, Andres (International Journal of Sustainable Energy Planning and Management, 2019)
The consumers are considered to play one of the most significant roles in the district heating transition process towards the 4th generation. Unfortunately, the lack of information and widespread consumer ignorance of interconnections and dependencies in the district heating system can lead to a situation where consumers are not interested in the development of the district heating system, or might even choose other heat sources. One of the possible solutions to provide information and educate consumers is a user-friendly, simplified mobile app that can show actual heat consumption structure, provide the possibility to compare the district heating supply with other heat supply solutions and provide information on how consumer behaviour affects the district heating system and how the district heating system transition towards the 4th generation will change the primary energy consumption and CO2 emissions. In this article, the authors present the concept and algorithm of a DHS promo mobile app that will be used at the national level in Estonia, that will allow consumers even with an insufficient amount of data available to each apartment/building owner to receive comprehensive information about the existing DHS and analyse how DHS improvements will affect the fuel mix and consumption amount required for heat supply per consume.